PEMANFAATAN TEKNOLOGI INFORMASI DALAM KEGIATAN DAKWAH TERHADAP TRANSFORMASI SOSIAL DI DESA MONTONG GAMANG KECAMATAN KOPANG KABUPATEN LOMBOK TENGAH-NTB - Ferdiansyah, Daeng Sani (KOMUNIKE, 2020)
Rapid environmental changes as a result of globalization and the development of science and technology, it must be acknowledged that it has provided islamic propaganda activities. On the other hand, reises concems about the development of behavior especially our young generation, with the emergence of a new life culture that tends to move away from the values of spirituality. Islamic propaganda must be made as attractive as possible by utilizing information technology as the main tool from the positive side, the devolopment of information technology has rasied strong awareness among some of our young generation of the inportance of having expertise and the main skill is to support a better future life, in order to fill the third melenium era which is reffered to as the information age and this technology has at least led to an optimistic attitude, our young generation in general has had the readiness to face these changes.